Ocular findings in Colombian patients affected with Fabry disease Manifestaciones oculares de enfermedad de Fabry en pacientes colombianos Ocular findings in Fabry disease (2019)
Fabry disease is a rare X-linked disorder caused by alpha-galactosidase enzyme deficiency, which leads to a progressive lisosomal glycosphingolipids accumulation, mainly globotriaosylceramide, in multiple organism tissues including the eye. This case series describes the first ophthalmological Colombian report of Fabry Disease highlighting the importance of ocular signs as markers of the disease, useful in diagnosis and treatment in order to avoid long-term complications that lead to a morbi-mortality increment. We describe five cases of Fabry disease from Bogotá, Colombia, including a complete clinical history, ophthalmologic, optometric examination, and photographs. We found that all patients had refractive defects and that in all cases corneal verticillata pattern was found. Four patients presented with posterior capsule lens brown-beige deposits, and four patients had conjunctival and retinal tortuous vessels. A complete ophthalmologic examination is important for prompt diagnosis, which is key to starting a multidisciplinary treatment and reducing morbi-mortality. © 2019, Instituto Nacional de Salud.